Using AI to Auto-Tag Graduate Theses. - Morgan, Kyle (Information Technology & Libraries, 2025)
This article presents a practical approach to using artificial intelligence (AI) for tagging graduate theses in an institutional repository with the United Nations Sustainable Development Goals. Utilizing strategies requiring no prior programming experience, the article provides a step-by-step guide, cost analysis, and lessons learned from employing two AI-based tagging methods. These methods, attempted with varying degrees of success, highlight the real potential of using AI for the thematic tagging of digital library resources.